(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Onopa V. M. Didactics, methodology, pedagogical technology and modeling of educational and cognitive processes. There are given the logic-semantical analysis and the scientific reliability of definitions «didactics», «methodology», «pedagogical technology» in this article. There are disclosed psychologic-pedagogical and methodologic-organizing aspects of technological modeling in it. There are proposed structural-functional models of educational process which must provide the strength of knowledge.